Literature review and case report of bilateral extensive psoas abscess: a rare case of spondylomyelitis with infection spread to Hunter's canal with rare causative microorganism - Nagaretnam, Vinodharan; Rampal, Sanjiv; Abas, Razif; Chopra, Suresh; Teh, Hak Lian (Turkish Joint Diseases Foundation, 2021)
A 43-year-old male patient with underlying diabetes mellitus presented with lower abdominal pain radiating to left thigh. He was hemodynamically stable, but appeared lethargic. Both iliac fossae were tender, and crepitus appreciated along the anteromedial aspect of the left thigh. The patient initially responded well to treatment and was discharged; however, he was re-admitted several months later due to recurrent collection showing the growth of Klebsiella pneumoniae in the culture and succumbed to sepsis due to deep-seated intramuscular abscess and lung empyema. In conclusion, psoas abscess is a condition that can mimic various pathologies related to the lower abdomen and, therefore, clinicians should always have a high index of suspicion to prevent a missed diagnosis. Early detection may yield good outcomes, if managed with adequate surgical drainage and appropriate antibiotics.